Utilizing Educational Technology and Its Application on PAI Learning - Bayu Bambang Nurfauji; Fikri Audah NSY; Aan Hasanah; Bambang Samsul Arifin (Edumaspul: Jurnal Pendidikan, 2023)
This research focuses on the use of educational technology in learning Islamic Religious Education (PAI) and the challenges it faces. Educational technology, which involves the application of scientific and technical principles and theories to the teaching-learning process, has shown significant potential to enrich learning methods and facilitate access to diverse learning resources. Some examples of its application in PAI include the use of Al-Qur'an applications, videos and animations, online discussion forums, and Islamic educational games. However, this research also found various challenges, including limited infrastructure, lack of digital literacy, and the need to adapt learning methods from conventional to digital. To overcome this challenge, this research suggests the need for developing technological infrastructure, increasing digital literacy, and further research on the adaptation of digital learning methods in the context of PAI. This research shows that, despite the challenges, educational technology has great potential to enrich Islamic education learning and provide better and more flexible learning opportunities for students